Following Up on Clinical Recommendations in Transitions from Hospital to Nursing Home. (9th February 2014) - Caruso, Lisa B.; Thwin, Soe Soe; Brandeis, Gary H.
Abstract : Following up on recommendations made at the time of a hospital discharge is important to patient safety. While data is lacking, specifically around the transition of patient to nursing home, it has been postulated that missed items such as laboratory tests may result in adverse patient outcomes. To determine the extent of this problem, a retrospective cohort study of subjects discharged from an academic medical center and admitted to nursing homes (NH) was followed to determine the type of discharge recommendations and the rate of completion. In addition, for the purpose of generalizability, the 30-day hospital readmission rate was calculated. 152 recommendations were made on 51 subjects. Almost a quarter of the recommendations made by the hospital discharging team were not acted upon. Furthermore, for the majority of those recommendations that were not acted upon, a reason could not be determined. In concert with national data, 20% of the subjects returned to the hospital within 30 days. Further investigation is warranted to determine if an association exists between missed recommendations and hospital readmission from the nursing home setting.